Issues, effects and implications of the Free Area of the Americas (FTAA) Agreement for CARICOM economies (ECLAC Port of SpainTT, 2004)
Analyzes some of the main issues, effects and implications of the FTAA for Caricom economies. Considers also, when relevant and for comparison purposes the cases of non independent states. Looks at the institutional and economic context of CARICOM. Describes the state of progress in the creation of the Single Market and Economy and the main traits on intraregional trade. Examines the extraregional performance of CARICOM in goods and services in relation to FTAA trade partners. Analyzes the potential effects of tariff reductions focusing on price and government revenue effects.
Keywords: FREE TRADE AREAS